THE CHARACTERISTICS OF EFFECTIVE ENGLISH TEACHERS: JUNIOR HIGH SCHOOL STUDENTS' PERCEPTIONS : A CASE STUDY IN A JUNIOR HIGH SCHOOL IN BANDUNG - Aldila, Chika (2016)
This study aims to investigate the characteristics of effective English teachers and the most important categories of the characteristics of effective English teachers based on junior high school students' perceptions. The study is based on the theory by Brown (2000) regarding the characteristics of effective English teachers; technical knowledge, pedagogical skills, interpersonal skills, and personal qualities. The study employed case study design. Eighteen students from the ninth grade of a public junior high school in Bandung were selected as the participants of the study. Thirty item questionnaires and a semi-structured interview were used as the instruments. The findings of the study indicated that students perceived characteristics of effective English teachers such as "easy to forgive", "not easily irritated", "appreciate students' differences", "able to speak in English", "able to treat students fairly", "increase students' motivation", "friendly and humorous", and "available for the students". Then, teacher's interpersonal skills and personal qualities are perceived by the students as the most important categories. Based on the findings, English teachers need to put a big concern in developing good interpersonal and personal qualities in order to be effective English teachers for junior high school students. Without developing a good interpersonal relationship with the students, teachers' knowledge and teaching skills would not be useful in the classroom.